Spatiotemporal Dynamics of Urban and Rural Settlements in Tanzania (1975–2020): Drivers, Patterns, and Regional Disparities - Jiaqi Zhang; Rongrong Zhang; Jiaqi Fan; Xiaoke Guan; Hui Liang (Land, 2025)
Exploring the spatiotemporal evolution of urban and rural settlements in African countries could provide critical insights into the patterns of urbanization, regional disparities, and sustainable development in the context of rapid socio-economic and demographic changes. Using global human settlement data alongside multi-source socio-economic and environmental datasets, this study investigates the spatiotemporal dynamics of human settlements in Tanzania from 1975 to 2020. A combination of methods, including hotspot analysis, standard deviation ellipse analysis, and geographic detectors, is employed to examine the characteristics of settlement evolution and the underlying factors contributing to regional differentiation. The findings reveal that over the past 45 years, the expansion of urban centers and urban clusters in Tanzania has significantly accelerated, while rural areas have experienced a corresponding decline, reflecting a shift from low-density to high-density settlements and a transformation from rural to urban landscapes. Dar es Salaam, Mwanza, and Arusha have consistently been hotspots for urban center growth, while Kagera has emerged as a primary hotspot for urban clusters. The distribution of rural hotspots and coldspots generally mirrors that of urban clusters. The spatial distribution of urban centers, urban clusters, and rural areas follows a northwest–southeast orientation, with the spatial distribution of urban centers gradually stabilizing. However, the development gap between urban clusters in the northwest and rural areas in the southeast is widening and narrowing, respectively. Socio-economic factors exert a stronger influence on the development of settlements than natural environmental factors. Population density, GDP density, and road network density are significant drivers of settlement patterns, with their influence intensifying over time.